Kategori dan Fungsi Sosial Cerita Rakyat di Nagari Guguak Sarai - Sari, Inda Fahmi; Tamsin, Andria Catri; Hamidin, Hamidin (Universitas Negeri Padang, 2012)
Purpose of this article is (1) to describe the category of folklore in the Nagari Guguak Sarai, (2) describe the social function of folklore in Nagari Guguak Sarai. The data in this study is the category of folklore and social functioning in the Nagari Guguak Sarai. The data source of this study is the story Asal Mula Nama Nagari Guguak Sarai, Nyiak Bulek, dan Batang Aia Panggadih. Data collected by recording techniques, notes, and interviews. The findings of the study at the folklore category Nagari Guguak Sarai categorized into local legends and legends individuals. Social function folklore Nagari Guguak Sarai is the identity, traditions, inherited, and educate.